When men think private thoughts - MacDonald, Gordon (Atlanta, GA Thomas Nelson, 1996)
Includes bibliographical references and study guide.
Keywords: Men (Christian theology).; Identity (psychology) -- religious aspects -- Christianity; Intimacy (psychology) -- religious aspects -- Christianity; Self perception in men; Men -- psychology; Masculinity (psychology) -- religious aspects -- Christianity